2014
DOI: 10.1186/2191-5040-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Vhub: a knowledge management system to facilitate online collaborative volcano modeling and research

Abstract: Knowledge of volcanic systems and the hazards they produce is rapidly advancing as internet resources become more readily accessible, new and more sensitive field techniques are developed, and ever greater amounts of data are collected. Such rapid advances drive the need for an online collaborative knowledge management system that enables the sharing of volcanological information, and modeling and analysis tools. Vhub (http://vhub.org) is a community cyberinfrastructure platform designed for collaboration in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…They found that collaboratively building a physical, 3D geographic model of place empowered the community to engage in constructive dialogue about hazard and risk. Such approaches also offer a way to integrate scientific and local knowledge in a way that is tangible and meaningful for many different people in the community, from government officials to school students (Cadag and Gaillard 2012 Palma et al 2014), local online hubs, such as wikis (Leonard et al 2014), and interactive online tools for volcanic hazard assessment, such as G-EVER (Tsukuda et al 2012), are helping to facilitate data-sharing and improve access to hazard modelling, enabling new levels of engagement and access to tools and information for map-making and design. While visual design of hazard maps will continue to evolve with innovation of new technologies and hazard mapping approaches, hazard map audiences will also evolve.…”
Section: Visualising Hazard In Different Formatsmentioning
confidence: 99%
“…They found that collaboratively building a physical, 3D geographic model of place empowered the community to engage in constructive dialogue about hazard and risk. Such approaches also offer a way to integrate scientific and local knowledge in a way that is tangible and meaningful for many different people in the community, from government officials to school students (Cadag and Gaillard 2012 Palma et al 2014), local online hubs, such as wikis (Leonard et al 2014), and interactive online tools for volcanic hazard assessment, such as G-EVER (Tsukuda et al 2012), are helping to facilitate data-sharing and improve access to hazard modelling, enabling new levels of engagement and access to tools and information for map-making and design. While visual design of hazard maps will continue to evolve with innovation of new technologies and hazard mapping approaches, hazard map audiences will also evolve.…”
Section: Visualising Hazard In Different Formatsmentioning
confidence: 99%
“…The Titan2D User Guide (http://vhub.org/resources/300) contains a detailed description of the TITAN2D model and some information on the preparation of the inputs for the standalone version of the code. (Palma et al, 2014). Funded by the U.S. National Science Foundation since 2010, the overarching goal of VHub is to provide a mechanism for globally collaborative research and development of computational models of volcanic processes and their integration with complex geospatial, observational, and experimental data.…”
Section: User Interactionmentioning
confidence: 99%
“…VHub also provides a mechanism for collaborative efforts at code development, verification, validation, and benchmarking. To take advantage of these capabilities the user must be registered on VHub (at no cost) and logged in to their account (Palma et al, 2014).…”
Section: User Interactionmentioning
confidence: 99%
“…This software provides an opportunity for students to take advantage of technology facilities [5], interaction with a wider and access more diverse range of authentic information sources based on the real data of volcanic activity in Indonesia which less underutilized as a learning resource. This model becomes a virtual media to provide knowledge about geoscience and can be used to exercise the geosciences skills to equip students to be more capable to solve the problems based on the real of geological data [7], to describe basic geosciences phenomena in the various contexts [8], to get better understanding the science behind phenomena [9], and help students to understand volcanic activity that cannot be directly observed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was necessary designing a simulation media that was able to accommodate the students' requirement in learning about geosciences concept interactively as an effort to encourage geoscience skills [3]. Many volcanic simulation programs have been developed by geoscience educators and researcher at the international level, including Computer Aided Instruction or CAI [3], Interactive Virtual Earth Science Teaching or InVest [4], Vhub [5], MIAVITA [6]. These programs proved able to support the community to understand the phenomenon of the volcano but it must be modified and adapted according to the physics students need in order to improve geoscience knowledge and predicting skills based on volcanic activity in Indonesia.…”
Section: Introductionmentioning
confidence: 99%